Capital gains taxation : a comparative analysis of key issues - Littlewood, Michael, 1960-; Elliffe, Craig, 1961- (Edward Elgar Publishing, 2017)
Capital gains taxes pose a host of technical and political design problems and yet, while the literature on the theory of capital gains taxation is substantial, little has been published on how governments have addressed these dilemmas. Written by a team of distinguished international experts, Capital Gains Taxation addresses the gap in the literature; it explains how a number of countries tax capital gains and the successes and pitfalls of these methods. Examining key issues in the theory and practice of capital gains taxation in a general context, this book also provides a detailed analysis of the tax systems of Australia, Canada, China, India, the Netherlands, New Zealand, South Africa, the UK and the US. It questions whether capital gains should be taxed in the same way as ordinary income, considers the rate at which they ought to be taxed, if indeed they should be at all, and compares the taxation on realisation of capital gains versus on an accruals basis. Eloquent and astute, Capital Gains Taxation will be a crucial point of reference for students and scholars of tax law and policy. Its pragmatic approach will also benefit tax practitioners, policy-makers and tax authorities.